Development and Validation of a New Design Self assessment logMAR Visual Acuity Test (“Chudjane” iPhone and iPad-based Application) in a Normal Eyes Population - Rodanant N. (2023)
Objective: To validate and further design the “Chudjane” application (app), a new design self-assessment logMAR test for distance visual acuity (VA), by comparing the results against the use of a standard numeric ETDRS chart in normal eye population. Materials and Methods: In total, 52 volunteers who had a normal eye exam and best-corrected VA score by numeric ETDRS (NE) chart equal to or better than 6/6 (logMAR score 0.00 or less) were included. The “Chudjane” app with 3 patterns of optotypes (Arabic numbers (AN), Tumbling-E (TE) and Landolt-C (LC)) was used twice to assess VA individually. Results: The mean VA in each test NE, AN, TE, LC from the first round were -0.06, -0.10, -0.08 and -0.04, respectively compared to -0.07, -0.12, -0.09 and -0.05 from the second round respectively. Comparing results from the first and second round revealed that NE and LC had higher test-retest reliability (ICC=0.712, 0.789 respectively) than AN and TE (ICC=0.140, 0.495 respectively). For validity, result from NE was compared to each app test using the second round values. Modified Bland-Altman plot showed the mean differences (95% LOA) for NE-AN, NE-TE and NE-LC of 0.05 (-0.11 to 0.20), 0.02 (-0.11 to 0.15) and -0.03 (-0.19 to 0.13) respectively. Simple linear regression analysis of the difference (i.e. NE-AN, NE-TE and NE-LC) on NE showed that the difference did not depend on the NE value with slope close to zero. Conclusion: The study demonstrated that by using the «Chudjane» application, LC had higher test-retest reliability and higher validity than TE and AN compared to the standard ETDRS chart.